2017
DOI: 10.1177/0003702817693239
|View full text |Cite
|
Sign up to set email alerts
|

Emission Characteristics of Laser-Induced Plasma Using Collinear Long and Short Dual-Pulse Laser-Induced Breakdown Spectroscopy (LIBS)

Abstract: Collinear long and short dual-pulse laser-induced breakdown spectroscopy (DP-LIBS) was employed to clarify the emission characteristics from laser-induced plasma. The plasma was sustained and became stable by the long pulse-width laser with the pulse width of 60 μs under free running (FR) conditions as an external energy source. Comparing the measurement results of stainless steel in air using single-pulse LIBS (SP-LIBS) and DP-LIBS, the emission intensity was markedly enhanced using DP-LIBS. The temperature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…For example, they proposed the collinear long and short DP-LIBS to detect the solid sample. The results showed that the plasma became more stable and sustained when using a long pulse-width laser (pulse width of 60 µs) as external energy, and marked enhancement were obtained compared to single-pulse LIBS [50]. Further, the spectral signal was enhanced about 3-7 times by long-short DP-LIBS comparing to conventional SP-LIBS when detecting the standard steel samples [51].…”
Section: Double Pulse Methodsmentioning
confidence: 97%
“…For example, they proposed the collinear long and short DP-LIBS to detect the solid sample. The results showed that the plasma became more stable and sustained when using a long pulse-width laser (pulse width of 60 µs) as external energy, and marked enhancement were obtained compared to single-pulse LIBS [50]. Further, the spectral signal was enhanced about 3-7 times by long-short DP-LIBS comparing to conventional SP-LIBS when detecting the standard steel samples [51].…”
Section: Double Pulse Methodsmentioning
confidence: 97%
“…Thus FR laser pulse has lower energy density which is not enough to produce an observable plasma emission. [25][26][27] A short pulse laser with wavelength of 1 064 nm, pulse width of 5-8 ns, pulse energy of 24.5 mJ and frequency of 10 Hz is generated by the Laser (LOTIS TII, LS-2134U). The reflected short pulse laser beam combined with the long pulse laser beam by polarization prism to realize the collinear long-short DP-LIBS.…”
Section: Methodsmentioning
confidence: 99%
“…It demonstrated the feasibility and enhanced detection ability of long-short DP-LIBS method due to pre-heating and re-heating effects of long pulse. [25][26][27] In this paper, the collinear long-short DP-LIBS was employed to discuss the sample temperature effect on steel measurement for the improvement of LIBS technique. The standard steel sample with different sample temperature was measured by single pulse LIBS (SP-LIBS) and collinear long-short DP-LIBS respectively to systematically study the sample temperature effects for steel measurement.…”
Section: Sample Temperature Effect On Steel Measurement Using Sp-libsmentioning
confidence: 99%
“…The long and short double-pulse LIBS method was proposed by our group and it has been named as LS-DP-LIBS [28,29]. In previous studies [30,31], LS-DP-LIBS has been compared with SP-LIBS based on the measurement results in an air atmosphere.…”
Section: Introductionmentioning
confidence: 99%